Subacute necrotizing encephalopathy (Leigh syndrome): report of two juvenile cases with fatal outcome - Göğüş, Safiye; Yalaz, Kalbiye; Güçsavaş, Müge; Akçören, Zuhal (The Turkish Journal of Pediatrics, 1994)
The clinical and pathological findings of two children diagnosed on autopsy with subacute necrotizing encephalopathy (SNE) are presented. One of the patients was a previously healthy 12-year-old boy with a rapid clinical course and fatal outcome. The second case was a mentally retarded 13-year-old girl with a positive family history of neurological disease and progressive deterioration.Brain edema, bilaterally symmetric gray-brown areas of spongy degeneration and cavity formation were present in the basal ganglia in both cases. A small cavity was noted in the right inferior olive in Case 2. Mamillary bodies were spared in both cases macroscopically and microscopically.Microscopic sections of the involved areas and the periaqueductal region in Case 2 exhibited variable degrees of necrosis, spongiosis with a striking proliferation, and dilatation of the capillaries. Similar changes were noted in the cerebral cortex of Case 1. Microglial and astrocytic proliferation with some loss of myelin were also noted. The neurons, although reduced in number, were frequently preserved within the lesions.To our knowledge, only three patients over two years old have been reported in the literature with an acute clinical course and a fatal outcome. Case 1 is the fourth such case.
Keywords: subacute necrotizing encephalo (myelo) pathy; Leigh syndrome; mitochondrial cytopathy